The Problems of Legal Regulations, Protection and Use of Groundwater (International Experience and Practice in Kazakhstan) - Yerkinbayeva, Lazzat; Sherimova, Nurzat; Borodina, Alina (International Journal of Sustainable Energy and Environmental Research, 2016)
This paper explored the main features of the legal regulations regarding the protection and use of groundwater in modern Kazakhstan. Other nations experience on these laws in light of negative anthropogenic influences will also be brought forth in the discussion of Kazakhstan’s water sources. These two topics along with related laws put forward by to improve subsoil, will be tied together to present a critical analysis of current water legislation within the Republic of Kazakhstan.